Journey across extrinsic tactics for power improvements of triboelectric energy harvesting beyond intrinsic materials and device structures: A concise review - Ahmed Mahfuz Tamim; Yebin Lee; Jung Hwan Park; Geon-Tae Hwang; Chang Kyu Jeong (Nano Trends)
The swift evolution of technologies like the Internet of Things (IoT), artificial intelligence (AI), and big data has created an unparalleled need for self-powered sensors and devices. While traditional power sources such as batteries remain in use, triboelectric nanogenerators (TENGs) have emerged as a promising alternative, capable of converting mechanical energy into electrical energy to power these sensors and devices. However, the practical application of TENGs largely depends on their power output and efficiency. The most promising approaches involve the optimization of material selection, surface modification, and chemical modification techniques to increase the triboelectric effect. Additionally, innovative device designs and charge mechanisms have evolved to improve charge generation and transfer mechanisms, thereby boosting TENG output. This review examines recent progress in methods to improve the power output and power density of TENGs. Rather than concentrating solely on approaches such as material selection, surface modification, or chemical modification, this review explores various strategies for enhancing output power and power density based on solid-solid interactions and alternating current (AC) TENGs. This comprehensive analysis provides valuable insights into current developments in TENG technology, paving the way for future innovations aimed at creating high-performance, self-powered systems for next-generation applications.